Prediction of eye and hair pigmentation phenotypes using the HIrisPlex system in a Brazilian admixed population sample - Carratto, Thássia Mayra Telles; Marcorin, Letícia; do Valle-Silva, Guilherme; de Oliveira, Maria Luiza Guimarães; Donadi, Eduardo Antônio; Simões, Aguinaldo Luiz; Castelli, Erick C. [UNESP]; Mendes-Junior, Celso Teixeira (Springer Nature, 2021)
Human pigmentation is a complex trait, probably involving more than 100 genes. Predicting phenotypes using SNPs present in those genes is important for forensic purpose. For this, the HIrisPlex tool was developed for eye and hair color prediction, with both models achieving high accuracy among Europeans. Its evaluation in admixed populations is important, since they present a higher frequency of intermediate phenotypes, and HIrisPlex has demonstrated limitations in such predictions; therefore, the performance of this tool may be impaired in such populations. Here, we evaluate the set of 24 markers from the HIrisPlex system in 328 individuals from Ribeirão Preto (SP) region, predicting eye and hair color and comparing the predictions with their real phenotypes. We used the HaloPlex Target Enrichment System and MiSeq Personal Sequencer platform for massively parallel sequencing. The prediction of eye and hair color was accomplished by the HIrisPlex online tool, using the default prediction settings. Ancestry was estimated using the SNPforID 34-plex to observe if and how an individual’s ancestry background would affect predictions in this admixed sample. Our sample presented major European ancestry (70.5%), followed by African (21.1%) and Native American/East Asian (8.4%). HIrisPlex presented an overall sensitivity of 0.691 for hair color prediction, with sensitivities ranging from 0.547 to 0.782. The lowest sensitivity was observed for individuals with black hair, who present a reduced European contribution (48.4%). For eye color prediction, the overall sensitivity was 0.741, with sensitivities higher than 0.85 for blue and brown eyes, although it failed in predicting intermediate eye color. Such struggle in predicting this phenotype category is in accordance with what has been seen in previous studies involving HIrisPlex. Individuals with brown eye color are more admixed, with European ancestry decreasing to 62.6%; notwithstanding that, sensitivity for brown eyes was almost 100%. Overall sensitivity increases to 0.791 when a 0.7 threshold is set, though 12.5% of the individuals become undefined. When combining eye and hair prediction, hit rates between 51.3 and 68.9% were achieved. Despite the difficulties with intermediate phenotypes, we have shown that HIrisPlex results can be very helpful when interpreted with caution.
Keywords: DNA phenotyping; Forensic DNA phenotyping; Forensic genetics; Massively parallel sequencing; SNPs